Re‐evaluation of gellan gum (E 418) as food additive. (20th June 2018) - ; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Filipic, Metka; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of gellan gum (E 418) as a food additive. Following the conceptual framework for the risk assessment of certain food additives re‐evaluated under Commission Regulation (EU) No 257/2010, the Panel considered that adequate exposure and toxicity data were available. Based on the reported use levels, a refined exposure of up to 72.4 mg/kg body weight (bw) per day in toddlers at the 95th percentile was estimated. Gellan gum is unlikely to be absorbed intact and would not be fermented by human intestinal microbiota. There is no concern with respect to carcinogenicity and genotoxicity. No adverse effects were reported in chronic studies at the highest doses tested in mice and rats (3, 627 and 1, 460 mg gellan gum/kg bw per day, respectively). Repeated oral intake up to 200 mg/kg bw per day for 3 weeks had no adverse effects in humans. The Panel concluded that there is no need for a numerical acceptable daily intake (ADI) for gellan gum (E 418), and that there is no safety concern at the refined exposure assessment for the reported uses and use levels of gellan gum (E 418) as a food additive. The Panel recommended to better define the specifications of gellan gum including the absence of viable cells of the microbial source and the presence of polyhydroxybutyrate (PHB), protein and residual bacterial enzymatic activities.